Investigating the molecular mechanisms that control the transformation of leaves into floral organs. - Horgan, Kate (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2021)
Arabidopsis thaliana is the model plant which has been used to elucidate the molecular and genetic processes which underlie floral organogenesis. This is the process in which the four floral organs are formed which is mediated by four classes of master regulator transcription factors. Extensive research over the past three decades has illuminated how these factors control the formation of the floral organs, however the downstream processes of these master regulators is not well understood. This research aims to investigate the molecular mechanisms that control the transformation of leaves into the four floral organs. In particular, this research examines how the floral homeotic factor AGAMOUS regulates the genes involved in organ polarity specification.
APPROVED